"Risk It Out, Risk It Out": Occupational and Organizational Stresses in Rural Policing. (December 2018) - Ricciardelli, Rosemary
In rural areas, police experience unique work-related health and safety risks attributable to a multitude of factors, ranging from inaccessible backup to navigating inclement weather alongside geographic obstacles. Although the result of institutional and organizational structures, operational (job content) and organizational (job context) risk must be recontextualized in the rural context. In the current study, I contextualize understandings of risk, referring to a lack of safety shaped by either a physical, administrative, legal, or emotional feeling of vulnerability—or a combination of such—for rural officers that results from occupational experiences of understaffing and insufficient material resources. Drawing on transcripts from 14 focus groups with 49 officers across rank, I extrapolate the effects of understaffing on officer experiences of work-role overload and the resulting stress. Findings reveal how officers' perceptions of risk are impacted by such factors, and how risk is interpreted as either preventable (i.e., organizational) or unavoidable (i.e., operational). In this context, risk knowledges of occupational realities shape the occupational role and well-being of officers working in rural and remote detachments. Preliminary policy implications are presented.